THE ANALYSIS OF SEMANTIC GRAMMATICAL ERRORS IN VARIOUS ARABIC TRANSLATIONS - Shofa Musthofa Khalid; Anwar Sanusi; Deni Maulana; Tatang Tatang; Mohamad Zaka Al Farisi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This study aimed to reveal the semantic grammatical errors in the translation of various Arabic sentences into Indonesian. This study used a qualitative descriptive method with a content analysis model. The data sources in this study were five different Arabic sentences translated by the teacher who taught the heritage book in Islamic boarding schools, namely: jumlah muṡbatah (positive sentences), jumlah manfiyah (negative sentences), jumlah istifhamiyah (interrogative sentences), jumlah syarṭiyah (conditional sentence), and jumlah al-qasam (sentence of oath). After analyzing and discussing the data obtained, the researcher found that there were 70% morphological errors in the translated text results consisting of 51% noun errors (isim) and 19% verb errors (fi'il). Additionally, the researcher found 76% syntactic errors from the translated text, consisting of 10% word errors, 9% phrase errors, 29% clause errors, and 28% sentence errors.